Metabolic engineering of Escherichia coli carrying catechins biosynthesis genes of Camellia sinensis (L) kuntze - Umar, Kabir Mustapha (2012)
Catechins are the most abundant polyphenolic compounds found in green tea (Camellia sinensis) that have been shown to bioactively affect the pathogenesis of several diseases. The sources of these substances are solely from tea leaves, thus relying on agriculture which may result to shortages due to unfavourable environmental conditions. Metabolic engineering strategies have recently been developed for the standardized biosynthesis of flavonoids in recombinant microbial systems through incorporation of genes in the biosynthetic pathway. Nevertheless, none of these strategies have produced any of the major catechins. This study is aimed at metabolically engineering the production of pure catechins in E. coli carrying the metabolite genes involved in biosynthesis of catechins in Camellia sinensis. DNA from Camellia sinensis leaf tissues was extracted and isolated by optimization of extraction parameters. High yield of DNA up to 1251lglml was obtained from 0.3g of leaf tissue. The optimal extraction parameters were determined to be; precipitation time of 40 minutes, at SO°Cincubation temperature and 200/S00/1 00111 (EBAIEBB/SDS) of extraction buffer combinations. Three genes [CsF3H (l107bp), CsDFR (l044bp) and CsLCR (l044bp)] were amplified and cloned into pET expression vectors and transformed into E. coli BL21 (DE3) competent cells. Genes were expressed in ImM IPTG to produce proteins F3H (40kDa), DFR (45kDa) and LCR (3SkDa), with corresponding theoretical sizes as analyzed by SDS-PAGE. A mimicked biosynthetic pathway of catechin metabolite genes from Camellia sinensis consisting of CsF3H, CsDFR and CsLCR encoding flavanone 3 hydroxylase, dihydroflavonol 4- reductase and leucoanthocyanidin reductase respectively was designed and arranged in two sets of constructs in the following order: (a) A single promoter upstream of CsF3H followed by ribosome binding sequences both upstream of CsDFR and CsLCR; (b) Three different promoters and ribosome binding sequences each upstream of the three genes. Recombinant E. coli BL21 (DE3) harbouring the constructs were cultivated for 65 h at 26°C in M9 medium consisting of 40 gil glucose, 1 mM IPTG and 3 mM eriodictyol. Compounds produced were extracted from culture medium using ethyl acetate in alkaline conditions after I h at room temperature and identified by HPLC. Two of the four major catechins, namely, (-)-epicatechin (0.01 mg/l) and (-)- epicatechin gallate (0.36 mg/l) and two other types; (+)-catechin hydrate (0.13 mg/l) and (-)-catechin gallate (0.04 mg/l) were successfully produced. Optimization of process parameters using a face centred central composite design (FCCCD) consisting of 30 experimental runs involving 6 centre points was designed using MIN ITAB® software. Glucose concentration had the most significant effect followed by temperature on yield of catechins. The optimum conditions for engineering of catechin production from the recombinant E. coli strain was as follows: IPTG (0.9 mM), glucose (10.1 gil), eriodictyol (1.0 mM) and temperature (27.9°C) and were predicted to produce a response of 0.97 mg/l with 80.98% desirability. A verification experiment carried out using predicted optimum parameters, produced a yield (0.911 mg/l ) close to the predicted value in which the gallated catechins [(-)-epigallocatechin gallate) and (-)-epicatechin gallate] were metabolically engineered for the first time.